PELESTARIAN DOLANAN ANAK DI DUSUN SIDOREJO DESA SIDOREJO KECAMATAN KRIAN KABUPATEN SIDOARJO - Khoirul Ngibad; Ernawati Ernawati; Anis Putri Ambarwati; Ayu Putri C.; M. Ali Zainuddin; Nanda Ady Cahyono (LP2M Universitas Ibrahimy, 2020)
Sidorejo backwoods is backwoods located in the v Sidorejo illage, Krian District, Sidoarjo Regency. The condition of preservation of dolanan anak or traditional games in Sidorejo backwoods is currently very poor. Most children in Sidorejo backwoods are more familiar with modern games, such as: online games, playstation and others. Based on the results of a survey conducted by students of Kuliah Kerja Nyata (KKN) in Sidorejo backwoods, it can be seen that the community of Sidorejo backwoods less responsive to the activity of reviving dolanan anak.. Therefore, the aim of Community Service is to preserve local culture through dolanan anak which is one part of the core program carried out by students of KKN from Universitas Maarif Hasyim Latif in order to preserve the existing local culture. The community service activities that are conceptualized in Kuliah Kerja Nyata (KKN) scheme involved students of Universitas Maarif Hasyim Latif from various study programs guided by Field Supervisors. The implementation of community service begins with initial observations in the field of traditional games among school children from Dusun Sidorejo RW 04 and 05 and then determines the schedule of dolanan anak activities through traditional children's play followed by all children from Dusun Sidorejo RW 04 and 05. The results of this community service program have made the children more enthusiastic to revive the existing traditional games. The parents do not forbid their children to play traditional games so that it can support the success of programs run by students from Universitas Maarif Hasyim Latif in the village of Sidorejo.